2015
DOI: 10.9738/intsurg-d-14-00134.1
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Small Round Cell Tumor in Transverse Colon: Report of a Rare Case

Abstract: Desmoplastic small round cell tumor (DSRCT) is an extremely rare, highly aggressive, malignant tumor of undetermined histogenesis. Adolescent males are primarily affected with a typically abdominal or pelvic mass. Diagnosis is based on histologic analysis of biopsy and cytogenetic studies. Owing to the rarity of the tumor and the unusually aggressive presentation, treatment is challenging and has not been standardized. DSRCT has a very poor prognosis, with a median survival range of 17 to 25 months. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It formed a pathognomonic EWSR1-WT1 t(11;22)(p13:q12) chromosomal translocation that pairs the Ewing sarcoma (ES) gene (EWSR1) with the Wilm’s tumor suppressor gene (WT1). The functional loss of the WT1 tumor suppressor protein and the oncogenic effects caused by the aberrant 59 kDa fusion protein results in hundreds or thousands of nodules coating the intraabdominal serosal and subdiaphragmatic surfaces 1214…”
Section: Discussionmentioning
confidence: 99%
“…It formed a pathognomonic EWSR1-WT1 t(11;22)(p13:q12) chromosomal translocation that pairs the Ewing sarcoma (ES) gene (EWSR1) with the Wilm’s tumor suppressor gene (WT1). The functional loss of the WT1 tumor suppressor protein and the oncogenic effects caused by the aberrant 59 kDa fusion protein results in hundreds or thousands of nodules coating the intraabdominal serosal and subdiaphragmatic surfaces 1214…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic study shows unique (11:22), (p13:q12) translocation which resulted in an active fusion protein involving the Ewing sarcoma (EWS) and Wilms tumor (WT1) genes [ 4 ]. The presence of this translocation provides definitive diagnosis for DSRCT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent genomics analysis of mutational profiles indicated that epithelial-mesenchymal transition (EMT), immune response, and the DNA damage response (DDR) are associated with gene deregulation in DSRCT (35). Whole-exome sequencing of six consecutive pre-treated DSRCT samples identified 137 unique somatic mutations: 133 mutated genes were case-FIGURE 1 | Previous case reports reported primary sites of DSRCT, including kidney (2), bladder (3), pancreas (4), transverse colon (5), testes (6), ovary (7), mediastinum (8), pleura (9), lung (10), parotid gland (11), salivary glands (12), middle ear (13), sinonasal (14), orbital (15), intracranial cavity (16), subcutaneous site (17), femur (18), and bone of the hand (19). specific, and only 2 genes were overlapping among two cases but in different locations, which reveals the heterogeneity of the DSRCT genome.…”
Section: Mechanismmentioning
confidence: 99%